PENGEMBANGAN QUANTUM TEACHING BERBASIS VIDEO PEMBELAJARAN CAMTASIA PADA MATERI PERMUKAAN BUMI DAN CUACA - Dewi Ayu Sulistya (Universitas Muhammadiyah Surakarta, 2017)
The Research to motivate students learning and helping teacher to give theory by Quantum Teaching Development model by using audio visual media software based on camtasia studio 8, as a valid and practical learning media. The type of Research Used is Research and Development. The procedure in this development study apply the according to Borg and Gall with initial research and information collection, planning, product draft development, initial field trials, revision test of the results. The result of media validation at first stage media expert was 57,5% and stage 2 was 91,25%, second media expert validation was 95%, material validation result in first material expert of phase 1 was 55,71, and phase 2 was 95 , 71%, second material expert validation 95,71%, student response question 93,75%. Then camtasia based on audio visual media with quantum teaching media is valid and ready for field trial. Then the questionnaire responses of students as much as 92.68% and questionnaire teacher response learning media and learning materials 97% and 100%. So it can be concluded that the development of quantum teaching based on camtasia learning video is valid and practical so that motivated learning besides feasible use learning in Elementary School.